Special section on intelligent & fuzzy theory in engineering and science - Guarda, Teresa (2019)
In recent decades, in order to reflect the complex needs of the information society, the field of “Intelligence & Fuzzy Theory” has continuously expanded its themes and boundaries. As a result, many academic studies have attempted to address complex information science and technology issues from a broader perspective. Therefore, it is our pleasure to release this issue of Journal of Intelligent & Fuzzy Systems, which represents cross-cutting research in the field of information technology and artificial intelligence, involving social sciences and engineering technology. The key areas of the selected articles include algorithms, Internet of Things, and intelligent algorithms.